2014
DOI: 10.2139/ssrn.2553790
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Action Representations in Thematic Object Relations

Abstract: A number of studies have explored the role of associative/event-based (thematic) and categorical (taxonomic) relations in the organization of object representations. Recent evidence suggests that thematic information may be particularly important in determining relationships between manipulable artifacts. However, although sensorimotor information is on many accounts an important component of manipulable artifact representations, little is known about the role that action may play during the processing of sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…These differences may help explain the N400 scalp distributions that differed somewhat across the studies (ranging from frontal-central in, e.g., van Elk et al, 2010 to more clearly frontal, as in the current study). More generally, however, the relatively anterior N400 action-related priming effects seen in the present study and related previous studies suggest that access to action semantics (Bach et al, 2009; van Elk et al, 2008, 2010; also see Leshinskaya and Caramazza, 2016 for a discussion) may differ from access to semantic information with weaker relationships to sensory-motor attributes, such as seen in the taxonomic conditions here (see also Kalénine and Buxbaum, 2016; Tsagkaridis et al, 2014). 3 …”
Section: Discussionsupporting
confidence: 48%
“…These differences may help explain the N400 scalp distributions that differed somewhat across the studies (ranging from frontal-central in, e.g., van Elk et al, 2010 to more clearly frontal, as in the current study). More generally, however, the relatively anterior N400 action-related priming effects seen in the present study and related previous studies suggest that access to action semantics (Bach et al, 2009; van Elk et al, 2008, 2010; also see Leshinskaya and Caramazza, 2016 for a discussion) may differ from access to semantic information with weaker relationships to sensory-motor attributes, such as seen in the taxonomic conditions here (see also Kalénine and Buxbaum, 2016; Tsagkaridis et al, 2014). 3 …”
Section: Discussionsupporting
confidence: 48%
“…In both experiments, we used object-tool pairs that were thematically consistent or inconsistent. Notably, increasing evidence from studies using thematically related vs. unrelated pairs of objects suggests an involvement of the posterior parieto-temporal cortex (specifically, the temporo-parietal junction, the inferior parietal lobe, and the middle and superior temporal gyri) in objects' thematic relations processing [60][61][62][63] . Moreover, an increased left occipital cortex activation (ventral stream) has been reported when objects are correctly positioned for action, while the anterior regions of the dorsal stream (e.g., supplementary motor area) have been reported to be activated when the task required an action decision but objects were not in the correct position for the action 36 .…”
Section: Manipulation Aoi Functional Aoimentioning
confidence: 99%
“…This finding was further supported by converging evidence from two studies of individuals with left-hemisphere stroke. The first found that temporoparietal lesions specifically impaired sensitivity to thematic relations that involve action, such as wine bottle – corkscrew (Tsagkaridis, Watson, Jax, & Buxbaum, 2014). The second showed a behavioral association between recognition of meaningful gestures (action knowledge) and performance on thematic triads, and that this association was mediated by posterior temporal damage (Kalénine & Buxbaum, 2016).…”
Section: Systematic Review Of Dissociation Between Taxonomic and Them...mentioning
confidence: 99%